Seaweed restocking along the Chilean coast: History, present, and inspiring recommendations for sustainability - Oyarzo-Miranda, Carolina; Otaíza, Ricardo; Bellorín, Alexis; Vega, J.M. Alonso; Tala, Fadia; Lagos, Nelson A.; Oyarzún, Fernanda X.; Estévez, Rodrigo A.; Latorre-Padilla, Nicolás; Mora Tapia, Ana María; Figueroa-Fábrega, Luis; Jara-Yáñez, Roddy; et al. (Frontiers in Marine Science, 2023)
Several seaweed species are commercialized worldwide both due to high demand for food and feed and as a raw material for the extraction of phycocolloids such as agar, carrageenan, and alginates that are used broadly in the food, cosmetic, and pharmaceutical industries. Chile is the world’s leading marine seaweed biomass producer when it comes to the exploitation of natural kelp beds. This extraction pressure has persisted for decades and has resulted in a reduction in natural stocks along the benthic ecosystems of the Chilean coast. Over the last three decades, several strategies aimed at restoring seaweed stocks have been implemented (i.e., sexual and asexual reproduction, the use of spore-type propagules or fragments of thalli, and entire thallus transplants). Success rates have varied, but the biological feasibility of such strategies has been demonstrated for several species. However, technological improvements must be achieved to move from small-scale, pilot experiments to cost-effective restocking strategies that are easy to transfer to fisher communities and another end-user, scalable to marine field conditions, and socio-ecologically sustainable. Researchers in other geographic areas have explored similar pathways for developing kelp restocking strategies and have tackled the research gaps regarding its massification. This work summarizes the research activities carried out in recent decades in the search for sustainable strategies to restore algal stocks in Chile.